Reformasi regulasi negara atas kebebasan sipil: Analisis hubungan antara perlindungan anak, penanggulangan radikalisme, dan kebijakan kebebasan beragama dalam perspektif HAM indonesia - Mubarok, Muhammad Syafi’ul (Maliki Interdisciplinary Journal, 2026)
Freedom of religion, child protection, and radicalism are often viewed as separate issues, yet they reveal the same underlying pattern: the disharmony of civil liberty regulations in Indonesia. The central problem of this study is how these three issues reflect the state’s failure to consistently fulfill its human rights obligations whether in preventing excessive restrictions, providing adequate protection, or ensuring social justice. This research employs a conceptual approach with comparative and evaluative analysis of legal frameworks, empirical findings, and human rights literature. The analytical technique involves identifying policy interrelations and reassessing the state’s role in safeguarding civil liberties. The main findings indicate that the state tends to be repressive in matters of religious freedom, weak in child protection, and ineffective in addressing the structural roots of radicalism. These inconsistencies form a single pattern of regulatory disharmony that directly contributes to citizens’ vulnerability. Civil liberties reform thus becomes an urgent necessity. The findings imply the need for a regulatory framework that is more aligned with human rights principles and better able to protect citizens in a fair, balanced, and sustainable manner.